New route for preparation of luminescent mercaptoethanoate capped cadmium selenide quantum dots - Wankhede, Manoj E.; Inamdar, Shaukatali N.; Deshpande, Aparna; Thete, Aniket R.; Pasricha, Renu; Kulkarni, Sulabha K.; Harani, Santosh K. (Bulletin of Materials Science, 2008)
We report a synthesis of cadmium selenide quantum dots (Q-CdSe) by refluxing a mixture of cadmium acetate, selenium powder, sodium sulfite and 2-mercaptoethanol in N,N'-dimethyl formamide (DMF)/water solution. X-ray and electron diffractions suggest the formation of hexagonal phase of size quantized CdSe. Based on TEM analysis, the formation of nanoparticles with an average diameter of 3.5 +/- 0.5 nm is inferred. Their sols in DMF and dimethyl sulphoxide (DMSO) gave characteristic absorption peaks at 300 nm and 327 nm, which is attributed to the formation of high quality, size quantized CdSe particles. Extracted particles from the sol were readily redispersed in DMF and DMSO, which were diluted further with water without losing their optical and colloidal properties. FTIR spectroscopy suggested the formation of 2-mercaptoethanol thiolate on the particle surface, with free -OH groups available for linkage. Sols in DMSO and their solutions in water displayed an intense photoluminescence (PL).
Keywords: chalcogenides; Chemical synthesis; photoluminescence; semiconductor quantum dots